2018
DOI: 10.1101/481739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D status and risk of incident tuberculosis disease: a systematic review and individual participant data meta-analysis

Abstract: Background: Few studies have evaluated the association between pre-existing vitamin D deficiency (VDD) and incident TB. We assessed the impact of baseline vitamin D on TB risk. Methods:We assessed the association between baseline vitamin D and incident TB in a prospective cohort of 6751 household contacts of TB patients in Peru. We also conducted a one-stage individual participant data meta-analysis searching PubMed and Embase for studies of vitamin D and TB until December 31, 2017. We included studies that as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…While the trend between elevated vitamin D and absence of TB infection despite high TB-exposure reported here is consistent with results from existing literature 1,10 , a study in Gambian adults reporting higher serum vitamin D levels in adults with TB disease compared to household contacts 5 points towards variation in associations even within the same country.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While the trend between elevated vitamin D and absence of TB infection despite high TB-exposure reported here is consistent with results from existing literature 1,10 , a study in Gambian adults reporting higher serum vitamin D levels in adults with TB disease compared to household contacts 5 points towards variation in associations even within the same country.…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis of 3,544 participants included in prospective trials investigating vitamin D and TB risk found a median vitamin D level of 26 ng/mL ( 65.0 nmol/L; IQR 19.5-33.4 ng/mL) and a dose-dependent relationship between de ciency of vitamin D (<10ng/mL) and increased risk of incident TB, a nding which was signi cantly exacerbated by HIV 1 . The applicability of these ndings to the Gambian population being studied here is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies have reported the variation of the body mass index (BMI) among TB patients, before, during and at the end of TB treatment [10] and the underweight as a high risk factor for TB-speci c and non-TB-speci c mortality during anti-TB treatment [11]. There is also evidence that vitamin D [12] and vitamin A [13] concentrations in peripheral blood could affect the incidence and progression of TB. However, there is a gap in the literature about the evaluation of dietary patterns in the comorbid condition of TB and DM, and on whether such information may be useful to guide optimization of clinical management.…”
Section: Introductionmentioning
confidence: 99%